ANTIMICROBIAL SUSCEPTIBILITY OF STRAINS OF COAGULASE-POSITIVE STAPHYLOCOCCUS ISOLATED FROM MASTITIC BOVINE MILK. - CORRÊA, I.; CORREA, M. G. P.; MARIN, J. M. (Ars Veterinaria, 2008)
A total of 95 coagulase-positive Staphylococcus strains isolated from 635 samples of mastitic milk from 72 dairy farms, were characterized in relation to resistance to 15 antimicrobial drugs. Among the isolates, resistance to sulphonamide was most frequent (80.2%), followed by resistance to ampicillin (78.9%), penicillin (77.8%) and lincomycin (71.5%). Multidrugresistant isolates were extremely common, and almost all isolates also showed resistance to two or more drugs; only one isolate showed resistance to a single drug. These results are probably a consequence of the intensive use of antimicrobial drugs. KEY-WORDS: Coagulase-positive Staphylococcus. Mastitis. Multidrug resistance. Antibiotic.